2016
DOI: 10.3389/fpls.2016.00595
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Intra–Annual Density Fluctuations: Mind the Gaps

Abstract: Tree rings are natural archives of climate and environmental information with a yearly resolution. Indeed, wood anatomical, chemical, and other properties of tree rings are a synthesis of several intrinsic and external factors, and their interaction during tree growth. In particular, Intra-Annual Density Fluctuations (IADFs) can be considered as tree-ring anomalies that can be used to better understand tree growth and to reconstruct past climate conditions with intra-annual resolution. However, the ecophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 67 publications
(112 reference statements)
2
59
0
Order By: Relevance
“…The cell features of the tracheids differentiated during this second period of growth differ from those previously formed in latewood since their cell wall thickness to lumen diameter ratio is lower than what it is observed in latewood, resembling earlywood (Carvalho et al, 2015;Vieira et al, 2015). These earlywood-like cells are referred to as Intra-Annual Density Fluctuations (IADFs; Battipaglia et al, 2016;Campelo et al, 2007;De Micco et al, 2016).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The cell features of the tracheids differentiated during this second period of growth differ from those previously formed in latewood since their cell wall thickness to lumen diameter ratio is lower than what it is observed in latewood, resembling earlywood (Carvalho et al, 2015;Vieira et al, 2015). These earlywood-like cells are referred to as Intra-Annual Density Fluctuations (IADFs; Battipaglia et al, 2016;Campelo et al, 2007;De Micco et al, 2016).…”
Section: Introductionmentioning
confidence: 88%
“…Latewood IADFs are frequently observed in Mediterranean pines (Campelo et al, 2015;de Luis et al, 2011b;Olano et al, 2012;Rozas et al, 2011;Vieira et al, 2010;Zalloni et al, 2016), and depending http://dx.doi.org/10.1016/j.agrformet.2017.02.024 0168-1923/© 2017 Elsevier B.V. All rights reserved. on its position within latewood the IADF can be classified as type L, when the earlywood-like cells are within latewood, or type L + , when the earlywood-like cells are located between latewood and the earlywood of the following tree-ring (Battipaglia et al, 2016;Campelo et al, 2007). Correlation analysis between the frequency of latewood IADFs and climate has revealed that type L is triggered by precipitation events in late summer and early autumn, whereas type L + is related to autumn precipitation (Campelo et al, 2007;Vieira et al, 2010Vieira et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Species adjust their phenology to climate change by shifting or compressing growth and reproduction seasons according to specific regional environmental drivers, local adaptations, and individual plasticity to climate (Nord and Lynch, 2009;Diez et al, 2012). The Mediterranean climate is characterized by a summer drought that forces the cambium into a quiescent or dormant state (Cherubini et al, 2003;Vieira et al, 2014a;Vieira et al, 2015;Battipaglia et al, 2016). Xylogenesis studies in the region have observed that the growing season can stop after the summer, but, under specific climatic conditions associated with water availability, cambial activity can resume after the summer (Camarero et al, 2010;Vieira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…IADFs can be present in earlywood and latewood, being defined as latewood-like cells within earlywood (IADF type E) or by earlywoodlike cells within latewood (IADF type L; Campelo et al, 2007), respectively. In trees growing in the Mediterranean region, earlywood IADFs are formed in response to a drought period during spring and latewood IADFs by above average precipitation in fall (Battipaglia et al, 2016;Campelo et al, 2007). Due to its refined climatic signal, IADFs have been recently used to improve the climatic signal of treering width chronologies (Campelo et al, 2007;Vieira et al, 2010;Wimmer, 2002).…”
Section: Introductionmentioning
confidence: 99%